An improved automated immunoassay for C-reactive protein on the Dimension® clinical chemistry system. Issue 5 (2000) - Wei, Tie Q.; Kramer, Steve; Chu, Victor P.; Hudson, Dave; Kilgore, Daniel; Salyer, Sue; Parker, Grace; Eyberger, Amy; Arentzen, Rene; Koiv, Heikki
Abstract : Recent clinical data indicate that the measurement of the concentration of C-reactive protein (CRP) requires a higher sensitivity and wider dynamic range than most of the current methods can offer. Our goal was to develop a totally automated and highly sensitive CRP assay with an extended range on the Dimension ® clinical chemistry system based on particle-enhanced turbidimetric-immunoassay (PETIA) technology. The improved method was optimized and compared to the Binding Site's radial immunodiffusion assay using disease state specimens to minimize interference. Assay performance was assessed on the Dimension ® system in a 12-instrument inter-laboratory comparison study. A split-sample comparison (n = 622) was performed between the improved CRP method on the Dimension ® system and the N Latex CRP mono method on the Behring Nephelometer, using a number of reagent and calibrator lots on multiple instruments. The method was also referenced to the standard material, CRM470, provided by the International Federation of Clinical Chemistry (IFCC). The improved CRP method was linear to 265.1mg/l with a detection limit between 0.2 and 0.5mg/l. The method detects antigen excess from the upper assay limit to 2000mg/l, thereby allowing users to retest the sample with dilution. Calibration was stable for 60 days. The within-run reproducibility (CV) was less than 5.1% and total reproducibility ranged from 1.1 to 6.7% between 3.3 and 265.4mg/l CRP. Linear regression analysis of the results on the improved Dimension ® method (DM) versus the Behring Nephelometer (BN) yielded the following equation: DM = 0.99 × BN − 0.37; r = 0.992. Minimal interference was observed from sera of patients with elevated IgM, IgG and IgA. The recovery of the IFCC standard was within 100 ± 7 % across multiple lots of reagent and calibrator. The improved CRP method provided a sensitive, accurate and rapid approach to quantify CRP in serum and plasma on the Dimension ® clinical chemistry system. The ability to detect antigen excess eliminated reporting falsely low results caused by the prozone effect.